A Case of Bile Duct Carcinoma with a Portal Annular Pancreas - Kato, Hiroyuki; Kitashiro, Shuji; Okushiba, Shunnichi; Miyasaka, Daisuke; Ebihara, Yuma; Watanabe, Yusuke; Kawarada, Yo; Saikawa, Daisuke; Sasaki, Takeshi (The Japanese Journal of Gastroenterological Surgery, 2012)
There has been little report on the presence of a hypertrophic uncinate process of the pancreas wrapping the superior mesenteric vein , and has been described as a portal annular pancreas or circumportal pancreas. We recently experienced a case of a patient in whom the pancreatic uncinate process surrounded the superior mesenteric vein. An 84-year-old woman with jaundice was given a diagnosis of lower bile duct cancer, and underwent surgery. During pancreatoduodectomy, we found an anomaly of the pancreas encasing the superior mesenteric vein. A computed tomography (CT) scan confirmed that the main pancreatic duct was passing through the anterior portion of the superior mesenteric vein, and we performed standard dissection of the pancreatic parenchyma antecedent to the superior mesenteric vein. After exposing the main pancreatic duct, we dissected the retroportal region, and the anomalous pancreatic parenchyma with autosutures on the left border of the superior mesenteric vein. Postoperatively, a pancreatic fistula, classified as Group A according to the International Study Group on Pancreatic Fistulas Classification, developed but improved with conservative management.